Single-Well Modeling Study In Buzurkan Oil Field - Al-Attar, Mazin H.; Al-Jawad, Dr. Mohammed S. (Journal of Petroleum Research and Studies, 2011)
Single well modeling technique is considered as an important tool in simulation studies that deal with the near well issues (i.e. water coning, optimum perforation intervals, etc.); or it may be used in the determination of the final acceptability of the entire field model (1). In this study, this technique is adopted to study and characterize one of the producing wells in Buzurkan oil field which is BU-3. The probability of the increase of water production will be tested with different production schemes, because if the well has to produce with certain water rate, the surface facilities have to be designed to be suitable for that rate. Water saturation distribution around the well is also inspected through the history of the well to determine the reason behind water production. CMG simulator has been used to perform this study. The results matching are based on the pressure and the produced water cut history and show good match in both cases. The model showed that there is a significant increase in water production with increase of oil rate due to water coning.